2012
DOI: 10.1155/2012/497572
|View full text |Cite
|
Sign up to set email alerts
|

Caveolin 3, Flotillin 1 and Influenza Virus Hemagglutinin Reside in Distinct Domains on the Sarcolemma of Skeletal Myofibers

Abstract: We examined the distribution of selected raft proteins on the sarcolemma of skeletal myofibers and the role of cholesterol environment in the distribution. Immunofluorescence staining showed that flotillin-1 and influenza hemagglutinin exhibited rafts that located in the domains deficient of the dystrophin glycoprotein complex, but the distribution patterns of the two proteins were different. Cholesterol depletion from the sarcolemma by means of methyl-β-cyclodextrin resulted in distorted caveolar morphology a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Immunoblotting also confirmed the lower concentration of β-dystroglycan and the dystrophin-associated cytolinker desmoglein [38]. In contrast, isoforms of the plasma membrane scaffolding protein flotillin, which is closely associated with caveolin-3 within caveolar membranes that are void of the dystrophincomplex [58], was shown to be increased in the Dp427-deficient sarcolemma. An interesting new aspect of the muscular dystrophy-initiating disintegration of the dystrophin complex is the identification of a reduced expression of the heteropolymeric intermediate filament protein synemin, which was previously shown to be linked to dystrophin and utrophin [37].…”
Section: Discussionmentioning
confidence: 74%
“…Immunoblotting also confirmed the lower concentration of β-dystroglycan and the dystrophin-associated cytolinker desmoglein [38]. In contrast, isoforms of the plasma membrane scaffolding protein flotillin, which is closely associated with caveolin-3 within caveolar membranes that are void of the dystrophincomplex [58], was shown to be increased in the Dp427-deficient sarcolemma. An interesting new aspect of the muscular dystrophy-initiating disintegration of the dystrophin complex is the identification of a reduced expression of the heteropolymeric intermediate filament protein synemin, which was previously shown to be linked to dystrophin and utrophin [37].…”
Section: Discussionmentioning
confidence: 74%
“…In contrast, both Akt and STAT3 phosphorylation were significantly attenuated by caveola disruption with CD, indicating that caveolae are required for Akt and STAT3 activation but not vice versa. Of note, CD, always served as an agent of cholesterol depletion, disrupts the structure of lipid rafts and caveolae by reducing membrane-free cholesterol, which results in distorted caveola morphology and redistribution of the Cav-3 protein [39] and subsequently leads to altered cell signaling and function [40]. In the present study, we treated the isolated cardiomyocytes with CD for 1 h at the dose of 10 μ mol/L [34] and this dosage could disrupt caveola function without affecting Cav-3 expression in NAC- and RPC-treated cardiomyocytes exposed to HG and H/R (Figure 9(d)).…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the exception of flotillin-1 move in in the cells activated by rVvpM, it reported that flotillin-1 is independently regulated and does not strictly correlate with the expression patterns of caveolin family members (Volonte et al, 1999 ). Indeed, it reported that the distribution patterns of flotillin 1 did not change upon cholesterol removal (Kaakinen et al, 2012 ). Therefore, our result in the present study indicate that rVvpM initiates the organization of rafts and the spatial distribution of caveolin which are crucially dependent on lipid raft clustering in fraction 3.…”
Section: Resultsmentioning
confidence: 99%